1993
DOI: 10.1177/096032719302500106
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort from glare: The role of pupillary hippus 

Abstract: An infra-red pupillometer was used to record pupillary unrest, or hippus, on three observers at various steady illuminance levels. Frequency spectrum analysis of pupillary oscillations shows that, in logarithmic units, amplitude per unit frequency is a decreasing linear function of frequency, and that amplitudes are reduced at higher illuminance levels. Hippus was then recorded for one observer in the presence of extreme discomfort glare. The resulting frequency spectrum is very similar to spectra obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 2 publications
0
20
0
2
Order By: Relevance
“…46 Indeed, it has been demonstrated that an intact trigeminal nerve is necessary to experience visual discomfort. 47 More recently, however, Howarth et al 48 showed that hippus (an irregular oscillation of iris constriction and dilation under intense illumination) is not consistently associated with subjective reports of visual discomfort. However, they assessed the relationship between hippus and visual discomfort in only one subject.…”
Section: Discussionmentioning
confidence: 99%
“…46 Indeed, it has been demonstrated that an intact trigeminal nerve is necessary to experience visual discomfort. 47 More recently, however, Howarth et al 48 showed that hippus (an irregular oscillation of iris constriction and dilation under intense illumination) is not consistently associated with subjective reports of visual discomfort. However, they assessed the relationship between hippus and visual discomfort in only one subject.…”
Section: Discussionmentioning
confidence: 99%
“…inflammation of the eyes and lids); dry or watery eyes; itchiness; tense muscles; breakdown of vision, blurred or double vision; headaches or fatigue. Such symptoms can further lead to discomfort and stress [7]. Discomfort glare in interior lighting is quantified by the Unified Glare Rating (UGR), with maximum UGR limits given by standards for various applications that typically range from 13 to 28.…”
Section: Glare From Led Lightingmentioning
confidence: 99%
“…The few studies that have considered physiological correlates of discomfort have focused mainly on its efferent manifestations. Early work, for example, was concerned with pupil size fluctuations (Fugate and Fry, 1956), particularly pupillary hippus (an involuntary spasm of the pupil) (Fry and King, 1975;Hopkinson, 1956) but later work showed little correlation with pupil size fluctuations and discomfort glare (Howarth et al, 1993). Electromyographic techniques (EMG) have also been employed, which examined facial muscle activity under conditions of discomfort (Berman et al, 1994;Murray et al, 2002).…”
Section: Introductionmentioning
confidence: 99%